Prohibition of Marriage According to the Mandailing Christmas Custom, North Sumatra (Maqashid Sya'riah Analysis) - Mhd. Eko Nanda Siregar; Muhammad Syukri Albani Nasution; Imam Yazid (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
The prohibition of marriage in Mandailing custom is an attempt to maintain genealogy, maintain the kinship system (da lihan na tolu and partuturon) and prevent generations of offspring from various health impacts that may occur if the prohibited marriage is violated. In the maqasid sharia theory, paying attention to lineage and the quality and quantity of generations of offspring is highly recommended. So in order to maintain the existence of offspring so that it can take place it is recommended to choose a partner who can give birth to healthy and many offspring, and everything that can cause no offspring in both males and females should be avoided as much as possible. Relative (cousin) marriage is a form of marriage that is prohibited in Mandailing custom but not prohibited in Islamic law and the Compilation of Islamic Law. Various population studies and several studies on health explain that consanguineous marriages have health risks to the generations they are born with, such as cancer, mental, liver, stomach-gut, hypertension, hearing loss, heart disease, thalassemia and other defects in children.